Population and Noncompartmental Pharmacokinetics of Sodium Oxybate Support Weight‐Based Dosing in Children and Adolescents With Narcolepsy With Cataplexy. Issue 5 (18th April 2020) - Chen, Cuiping; Rosen, Carol L.; Ruoff, Chad; Boyce, Leslie H.; Parvataneni, Rupa; Zomorodi, Katie; Brantley, Scott; Sale, Mark; Plazzi, Giuseppe
Abstract : The pharmacokinetics (PKs) of sodium oxybate (SXB) was evaluated in a subset of participants from a study of SXB treatment in children (aged 7–11 years; n  = 11) and adolescents (aged 12–17 years; n  = 18) with narcolepsy with cataplexy. PK evaluation was conducted over 2 nights during the period when participants received a stable nightly SXB dose. The SXB dose on night 1 was half of night 2 and was administered in two equally divided doses: dose 1 was administered > 2 hours after the evening meal, and dose 2 was administered ≥ 4 hours after dose 1. Noncompartmental PK analysis demonstrated higher plasma concentrations post‐dose 2 vs. post‐dose 1, higher than dose‐proportional increases in area under the concentration‐time curve from 0 to 4 hours (AUC0–4h ) after dose 1, indicating nonlinear clearance, and better correlation between exposure and mg/kg than exposure and gram dose. To confirm the noncompartmental findings, identify factors affecting SXB PK, and compare with prior results in adults, a population PK (PopPK) model was established combining PK data from the current study with prior data from adults (132 healthy volunteers and 13 with narcolepsy). A two‐compartment PopPK model with first‐order absorption and nonlinear clearance from the central compartment described the data well. PopPK identified weight as the main intrinsic factor and food as the main extrinsic factor affecting SXB PK, and predicts similar PK profiles on a mg/kg basis across ages. These results, along with previously reported efficacy and safety outcomes, support weight‐based SXB dose initiation in pediatric patients.